Loan Loss Provisions Practices in Hong Kong Banking System - Dong, Mingrui (2015)
In the wake of the global financial crisis, the Basel Committee encourages a dynamic provisioning system. Reducing the pro-cyclical effect of loan loss provisioning is a way to achieve this. Therefore, this dissertation’s main objective is to determine if the provisioning system in Hong Kong commercial banks is pro-cyclical. Based on a sample of 35 commercial banks in Hong Kong ranging a decade from 2005 to 2014, and by applying the methodology of system GMM, this dissertation proves that the provisioning system in Hong Kong tends to follow a pro-cyclical pattern